Implication of Macroeconomic Factors to Stock Returns of Indonesian Property and Real Estate Companies - Maharditya, Muhammad Adika; Layyinaturrobaniyah, Layyinaturrobaniyah; Anwar, Mokhamad (JDM (Jurnal Dinamika Manajemen), 2018)
This study aims to identify the effect of interest rate change policy made by Bank Indonesia during the period of January 2010-March 2016 to stock return of the property sector and real estate. In addition, this study also aims to test whether fluctuations in government bond yields, inflation, and indigo exchange also affect the stock returns of the property sector and real estate in Indonesia. By using purposive sampling, there are 15 companies that will be used as research samples. By using multiple linear regression analysis, there is no significant negative effect of interest rate (BI Rate) and inflation on stock return of the property sector and real estate. Nevertheless, it was found that the variable fluctuation of government bond yield and dollar exchange rate against rupiah had a negative and significant effect on stock returns of property and real estate sector in Indonesia. Increased bond yield would make investors choose other instruments as an alternative to investing money. In addition, investors also tend to choose to save money in the form of US Dollar rather than investing money in the capital market, further with the weakening of the value of the rupiah will increase the amount of foreign debt from the company.